Residência multiprofissional em saúde: a formação em serviço no Brasil - Andrade, Kércia Rocha (2020)
The present study maps and analyzes the Multidisciplinary Residency in Health (Remu), in Brazil, seeking to identify the key historical elements, legal norms, particularities, and the extent of this modality of lato sensu education, thus, verifying the influence that medical education in the United States has on that of Brazil. As such, it is a reference, for both medical and multidisciplinary residency. Recognized as a lato sensu graduate program, the Multidisciplinary Residency in Health constitutes a modality of continued education in health designed for professionals with degrees in this realm, with the exception of doctors. In order to discover the nature of the Multidisciplinary Residency in Brazil, the following article investigates the evolution of residencies in health, identifying early examples within the country. Next, investigate the historical process, legal norms, and characteristics surrounding the Multidisciplinary Residency in Brazil. Finally, with the intention of analyzing the extent of the Multidisciplinary Residency in the country, performed a mapping this formation through the analysis of edicts from the selective processes. As such, a qualitative research featuring quantitative data is utilized, through a critical historical approach which facilitates reflection over Multidisciplinary Residency in the different regions of Brazil. To that end, this study utilizes 79 edicts for Multidisciplinary Residency in Health during the period of 2018 to 2020, of which 01 was selected per institution, corresponding to 07 from the North Region, 15 from the Northeast Region, 07 from the Center-West Region, 31 from the Southeast Region, and 19 from the South Region. It is concluded that, despite the growth of the Multidisciplinary Residency in Health in Brazil, there is still a need for expansion in the North and Center-West Regions, including but not limited to: demanding more equal distribution of job openings among the professions, improving spaces for social participation through collective reflection with regard to education in service, and finally, reaffirming Multidisciplinary Residency as a modality of education that allows for the improvement of services provided by the Unified Health System